New Tools for New Regional Policy in Central European Countries - Valeria Szitasiova; Miroslav Sipikal (European Regional Science Association (ERSA), 2013)
Regional policies were strongly related to the support of industries as automotive, wood- processing or engineering. However new important sectors as information technologies or creative industries has started to play more important role in the development of countries. These sectors require different approach by the implementation of development policies. The changed circumstances bring also changes in the design of regional policies and creation and implementation of regional strategies. The paper deals with new tools of regional policy regarding to the changed environment in Central European Countries. The first part includes a basic literature overview according to the research topic. The paper is analyzing the need of shifting regional policies for the lagging behind regions in Central European countries. We investigated used tools in the present regional policy. We conducted interviews with relevant companies and support institutions to identify their relevance and suggest changes for new programming period of regional policies in Central European countries.
Keywords: R11; R58; 330; Regional Policy; Creative Industries; Tools of Regional Policy